2018
DOI: 10.1161/hypertensionaha.117.10662
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone Versus Clonidine as a Fourth-Drug Therapy for Resistant Hypertension

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01643434.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
23

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(61 citation statements)
references
References 24 publications
2
36
0
23
Order By: Relevance
“… IIa B [ 133 , 134 ] • Loop diuretics can be considered in patients with CHF, advanced CKD of stage IV or stage V. IIa B [ 135 ] • In patients with resistant HTN, aldosterone antagonists such as spironolactone can be considered in the absence of hyperkalemia. IIa B [ 136 , 137 ] …”
Section: Chapter II Treatment Of Hypertensionmentioning
confidence: 99%
“… IIa B [ 133 , 134 ] • Loop diuretics can be considered in patients with CHF, advanced CKD of stage IV or stage V. IIa B [ 135 ] • In patients with resistant HTN, aldosterone antagonists such as spironolactone can be considered in the absence of hyperkalemia. IIa B [ 136 , 137 ] …”
Section: Chapter II Treatment Of Hypertensionmentioning
confidence: 99%
“…36 The second observation is that many patients with resistant hyperten sion can actually be conrolled using the pre scription of spironolactone as the fourthline therapy after diuretics, calcium antagonists, and RAS blockers. [37][38][39][40] Thus, the real need for an interventional therapy decreased signifi cantly as more precise data on resistant hy pertension were gathered.…”
mentioning
confidence: 99%
“…Data from clinical studies of spironolactone versus central acting drugs Although concrete evidence supports the superiority of mineralocorticoid receptor antagonists over alpha-and beta-blockers for patients with resistant hypertension, there is a lack of evidence regarding the use of central acting drugs in such patients. In this setting, the recent Resistant Hypertension Optimal Treatment (ReHOT) study compared the impact of spironolactone and clonidine in 187 patients with resistant hypertension 16 . BP control assessed with office and 24-hour ambulatory BP monitoring was similar across the two groups of patients.…”
Section: Recent Advances In Pharmacological Therapymentioning
confidence: 99%
“…Meta-analytic data of mineralocorticoid antagonists versus other drug classes Important information emerged from meta-analytic data for the use of mineralocorticoid receptor antagonists in patients with resistant hypertension. In 869 patients from four trials, spironolactone as add-on therapy was associated with a reduction in BP of 16.67/6.11 mm Hg 16 . A meta-analysis of 662 patients and five trials found that the addition of spironolactone in patients with resistant hypertension resulted in a reduction in office BP levels of 15.73/6.21 mm Hg compared with placebo, but compared with other drugs (beta-blocker, candesartan, or alpha methyldopa), spironolactone reduced home systolic BP by 4.5 mm Hg 18 .…”
Section: Recent Advances In Pharmacological Therapymentioning
confidence: 99%